Pembuatan Animasi Drawing untuk Meningkatkan Kemampuan Basic dan Technology Literacy Siswa SMPN Unggulan Sindang - Elin Herlina (Direktorat Guru Pendidikan Dasar, Kemendikbudristek R.I., 2022)
The purpose of the study is improving the Basic and Technology Literacy skills of VIII I SMPN Unggulan through Drawing Animations. This study used Qualitative Research Methods in the form of Classroom Action Research. The subject amounted 33 people. The techniques of collecting data were Observation Sheets, Product Assessment Sheets, Questionnaire Test. The results on the ability of Basic Literacy in Cycle I produced a concept map, the average score was 79, the highest score was 90, the lowest score was 75, 61% passed. In Cycle II, it produced Storyline the average score of 89, the highest score of 98, the lowest score of 80, 100% passed, student’s produced an Animation Drawing the average score is 89, the highest score is 98, the lowest score is 80, 100% passed. Cognitive learning outcomes in Cycle I the average score is 79, the highest score is 98, the lowest score is 38, 67% passed, in Cycle II the average score is 84, the highest score is 98, the lowest score is 63, 82% passed. The students'attitudes were 4 people high, 19 people moderate, 7 people low appreciation. This research proves by making an Animation Drawing, students'Basic and Technology Literacy abilities increased.